LITERATURE REVIEW: THE EFFECT OF BABY MASSAGE ON SLEEP QUALITY AND WEIGHT GAIN IN INFANTS - Aulia, Devy Lestari Nurul; Anjani, Arum Dwi; Octafera, Nasywa Putri (HEARTY, 2026)
Sleep disturbances and suboptimal weight gain remain common problems in infants, especially due to inadequate stimulation, discomfort, anxiety, or colic. One non-pharmacological intervention that is widely used is baby massage, which through touch stimulation can increase comfort, relaxation, and help regulate hormones involved in the sleep cycle and the infant’s body metabolism. This study aims to analyze the effect of baby massage on sleep quality and weight gain in infants. This study used a qualitative approach with a literature review method. Data sources were obtained from scientific journals, research reports, regulations, and other relevant literature. The literature selection process was carried out using the prisma flow, resulting in several studies that met the inclusion criteria to be analyzed qualitatively. The results showed that baby massage has a positive impact on sleep quality and infant weight gain. Baby massage performed routinely for approximately 30 minutes per day for two weeks was proven to reduce the frequency of nighttime awakenings and increase infant sleep duration. In addition, massage stimulation on the vagus nerve can increase digestive enzyme activity, accelerate gastric emptying, improve intestinal peristalsis, and enhance nutrient absorption, thereby contributing to weight gain in infants. In conclusion, baby massage is a simple, safe, and effective intervention in improving sleep quality and infant weight gain. The routine implementation of baby massage can be one of the recommended growth and development stimulation methods for parents and healthcare workers in supporting optimal infant health and development.